2017
DOI: 10.1371/journal.pone.0188071
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms of action of Coxiella burnetii effectors inferred from host-pathogen protein interactions

Abstract: Coxiella burnetii is an obligate Gram-negative intracellular pathogen and the etiological agent of Q fever. Successful infection requires a functional Type IV secretion system, which translocates more than 100 effector proteins into the host cytosol to establish the infection, restructure the intracellular host environment, and create a parasitophorous vacuole where the replicating bacteria reside. We used yeast two-hybrid (Y2H) screening of 33 selected C. burnetii effectors against whole genome human and muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 109 publications
(117 reference statements)
0
11
0
1
Order By: Relevance
“…Indeed chemical inhibition of the UPR antagonises the expansion of the CCV (Brann et al, 2020). Several C. burnetii effector proteins have been identified by a yeast‐based interaction screen to target ER host proteins (Wallqvist et al, 2017). One ER localised C. burnetii T4BSS effector protein is ElpA (Graham, Winchell, Sharma, & Voth, 2015; Weber et al, 2013), which triggers disruption of ER structure (Graham et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed chemical inhibition of the UPR antagonises the expansion of the CCV (Brann et al, 2020). Several C. burnetii effector proteins have been identified by a yeast‐based interaction screen to target ER host proteins (Wallqvist et al, 2017). One ER localised C. burnetii T4BSS effector protein is ElpA (Graham, Winchell, Sharma, & Voth, 2015; Weber et al, 2013), which triggers disruption of ER structure (Graham et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While great strides have been made toward understanding how effector proteins manipulate host processes to redirect membrane and nutrients to the parasitophorous vacuoles, the function of most effector proteins still remains ill-defined and genetic manipulation of some of these organism presents specific challenges. Large-scale screens to identify putative binding partners of ectopically produced type III secreted effectors (Mirrashidi et al, 2015 ) or yeast-2-hybrid screening of type IV secreted effectors (Wallqvist et al, 2017 ) has identified potential interacting partners for many previously uncharacterized effector proteins. While these seminal studies will serve as a useful starting point for elucidating effector function of uncharacterized secretion substrates, many of these interactions still require validation.…”
Section: Discussionmentioning
confidence: 99%
“…ORP1L acts as a cholesterol sensor that modulates the formation of MCSs between the late endosomes and the ER. It has been recently reported that Coxiella recruits ORP1L to MCSs formed between the bacterial inclusion and the ER, which is followed by changes in the membrane properties of the inclusion vacuole (Justis et al, ; Wallqvist et al, ). ORP1L attaches to the Coxiella ‐containing vacuole membrane through its N‐terminal ankyrin repeats that are involved in protein–protein interactions, but the specific function of ORP1L in the infection is still unclear.…”
Section: Bacteriamentioning
confidence: 99%